Чинники ризику розвитку фібропластичних процесів за цукрового діабету 2-го типу у віддаленні терміни після опромінення - Коваленко, О. М.; Муравйова, І. М.; Чикалова, І. Г.; Самойлов, О. О.; Пронін, О. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
The study involved 100 clean-up workers of the consequences of the Chernobyl accident divided into 2 subgroups: 50 patients with acute radiation sickness (ARS) exposed to doses over 1.0 Gy, 50 patients exposed to doses 0.3-0.9 Sv; 37 patients with diabetes mellitus in control group not exposed to ionizing radiation. Serum amino-terminal propeptide (PINP) and carboxy terminal telopeptide of collagen type I (ICTP) levels were greater in exposed patients with ARS having doses over 1.0 Gy than in those without. Clean-up workers exposed to doses 0.25-7.1 Gy have apparent disorders of configuration and dimensional change left ventricle of heart in preference at the expense of cardiac wall thickness and linear-volumetric dimensions of ventricular cavity against the background increase of systolic blood pressure and body mass index. At patients with ARS insulin relative insufficiency leads to inhibition of collagen I type degradation and its accumulation in extracellular matrix with fibroplastic process enhancement. This observation may help explain the complex changes in extracellular matrix after radiation impact and may suggest new ways for diagnostic and therapeutic interventions.